Aggressive lymphoma subtype is a risk factor for venous thrombosis. Development of lymphoma ‐ specific venous thrombosis prediction models. Issue 8 (8th May 2020) - Dharmavaram, Gouri; Cao, Shufen; Sundaram, Suchitra; Ayyappan, Sabarish; Boughan, Kirsten; Gallogly, Molly; Malek, Ehsan; Metheny, Leland; Tomlinson, Benjamin; Otegbeye, Folashade; Lazarus, Hillard M.; Cooper, Brenda; et al.
Abstract: Venous thromboembolic events (VTE) are a frequent complication of lymphoma. We conducted a retrospective analysis to compare VTE risk in diffuse large B‐cell lymphoma (DLBCL) and follicular lymphoma (FL). Subjects were randomly assigned to training and validation sets to identify risk factors of VTE and evaluate risk model performance, including the Khorana score. A group of 790 patients were diagnosed from 2002 to 2014 (DLBCL = 542, FL = 248). Median follow‐ up was 49 months. We observed 106 VTE, with higher incidence in DLBCL (5‐year cumulative incidence = 16.3% vs 3.8% in FL patients). Five‐year OS for patients with VTE was 51.4% vs 73.1% in patients without VTE ( P < .001). Baseline VTE risk factors identified in the training cohort included lymphoma subtype, previous VTE, ECOG performance status ≥2, decreased albumin, increased calcium, elevated WBC, absolute lymphocyte count or monocyte count, and presence of bulky disease. Addition of new variables to the Khorana score improved its performance measured by Akaike information criterion and Concordance index. A new risk model including lymphoma subtype, albumin, WBC count, and bulky disease was validated in time‐based ROC analyses. These findings were confirmed in the validation cohort. Lymphoma subtypes have different VTE risk. The effect of lymphoma subtype was independent from disease burden and the use of systemic therapy. The Khorana risk‐score was validated in time to event analyses, and a more robust lymphoma‐specific VTE risk score is proposed. These findings suggest lymphoma patients with highest VTE risk can be identified with baseline parameters.